The Effects of COVID-19 on Immune System and Diabetes - Beydoğan, Alişa Bahar; Kamer Çolak, Dilara; Bilge, Bilge Nur; Bolkent, Sema (Cerrahpaşa Medical Journal, 2020)
Severe acute respiratory syndrome (SARS) Coronavirus (CoV)-2 (SARS-CoV-2) disease (COVID-19), which first appeared in December 2019, has affected the whole world in about two months. COVID-19 was announced as a pandemic by the World Health Organization on March 11, 2020. Researchers have begun to study this disease because there is no treatment for COVID-19. In addition, the high incidence of individuals with chronic disease has encouraged researchers to hypothesize about the relationship of chronic diseases with COVID-19. Individuals with one or more chronic diseases such as hypertension, type-II diabetes, cardiac and renal insufficiency, and chronic lung diseases constitute the high-risk group. In addition, it is known that SARS-CoV-2 causes hyperinflammation. Diabetes can increase the risk of morbidity and mortality because of impaired immune system. The purpose of the present review is to explain the effects of COVID-19 on immune response by associating it with chronic diseases such as diabetes. Cite this article as: Beydoğan AB, Çolak DK, Bilge BN, Bolkent S. The Effects of COVID-19 on Immune System and Diabetes. Cerrahpaşa Medical Journal 2020; 44(2): 65-73.